2021
DOI: 10.1038/s41467-021-25309-9
|View full text |Cite|
|
Sign up to set email alerts
|

In situ ultrastructures of two evolutionarily distant apicomplexan rhoptry secretion systems

Abstract: Parasites of the phylum Apicomplexa cause important diseases including malaria, cryptosporidiosis and toxoplasmosis. These intracellular pathogens inject the contents of an essential organelle, the rhoptry, into host cells to facilitate invasion and infection. However, the structure and mechanism of this eukaryotic secretion system remain elusive. Here, using cryo-electron tomography and subtomogram averaging, we report the conserved architecture of the rhoptry secretion system in the invasive stages of two ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
118
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(137 citation statements)
references
References 63 publications
18
118
1
Order By: Relevance
“…Closer inspection of the IMT-aligned AVs revealed a density partially surrounding the vesicle in the majority (75%) of the tomograms, with a similar density also observed surrounding the AVs positioned anterior to the IMTs (S7A-D Fig). Using the tomographic data to examine this structure more carefully revealed that in at least 31 out of 48 tomograms the density partially coats the AVs, and in 10 instances it resembled the rosette that was previously characterized as part of the RSA found between the rhoptry-interacting AV and the parasite’s plasma membrane [19] (S8 A-D Fig). The difference in our data from those previously reported is that we observe these rosette-like structures associated with more than one AV in a single AC and even around AVs that are IMT-associated, not just those that are anterior-most or interacting with a rhoptry tip.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Closer inspection of the IMT-aligned AVs revealed a density partially surrounding the vesicle in the majority (75%) of the tomograms, with a similar density also observed surrounding the AVs positioned anterior to the IMTs (S7A-D Fig). Using the tomographic data to examine this structure more carefully revealed that in at least 31 out of 48 tomograms the density partially coats the AVs, and in 10 instances it resembled the rosette that was previously characterized as part of the RSA found between the rhoptry-interacting AV and the parasite’s plasma membrane [19] (S8 A-D Fig). The difference in our data from those previously reported is that we observe these rosette-like structures associated with more than one AV in a single AC and even around AVs that are IMT-associated, not just those that are anterior-most or interacting with a rhoptry tip.…”
Section: Resultsmentioning
confidence: 89%
“…The role of the AVs in rhoptry secretion has long been speculated [14, 30] and they were previously described in other apicomplexans, e.g. Cryptosporidium, Eimeria, Sarcocystis , and Besnoitia [1517, 19, 31]. Although no direct connection was detected between the IMTs or their associated AVs and the conoid fibrils, we did observe that the AVs are not centered or positioned randomly in the intraconoid space; instead, most were positioned to the side, as viewed from the top of the specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Toxoplasma gondii, sporozoites and merozoites are the invasive stages of C. parvum and possess a number of specialized subcellular structures, including rhoptries, micronemes, and dense granules (3)(4)(5)(6). Cryptosporidium parasites possess a secretory machinery composed of a single rhoptry, numerous micronemes, and a number of dense granules that are discharged during invasion (3,4,(7)(8)(9). The morphologies of the three secretory organelles in Cryptosporidium sporozoites and merozoites have been studied using transmission electron microscopy (TEM) (3,7,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptosporidium parasites possess a secretory machinery composed of a single rhoptry, numerous micronemes, and a number of dense granules that are discharged during invasion (3,4,(7)(8)(9). The morphologies of the three secretory organelles in Cryptosporidium sporozoites and merozoites have been studied using transmission electron microscopy (TEM) (3,7,(9)(10)(11)(12). The rhoptry is a single flaskshaped organelle whose tip is attached to the apical end of the parasite, with its end extending to slightly less than a third of the zoite.…”
Section: Introductionmentioning
confidence: 99%